2020
DOI: 10.33448/rsd-v9i3.2260
|View full text |Cite
|
Sign up to set email alerts
|

Formação permanente: contribuições para a prática pedagógica do enfermeiro

Abstract: Objective to reflect on continuing education as a contribution to the pedagogical practice of nurses in professional education. Study of qualitative approach of bibliographic research, which considered the works, Pedagogy of the Oppressed and Pedagogy of Autonomy, both by Paulo Freire. For such reflection, the following category was chosen: Nursing pedagogical practice and permanent formation in Freire. Thus, although nurses are educators and the undergraduate nursing enables broad performance, from the area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…It was also found that the first step in the teaching career took place through an invitation to teach a class, justified, in certain cases, by accentuated mastery of knowledge and successful professional performance. Such justification supports the mistaken idea that those who have expertise in certain content or broad professional experience necessarily know how to teach and that people learn to teach while teaching 15,18 . It is undeniable that the teacher must possess depth of knowledge of their subject matter, but not only of it.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was also found that the first step in the teaching career took place through an invitation to teach a class, justified, in certain cases, by accentuated mastery of knowledge and successful professional performance. Such justification supports the mistaken idea that those who have expertise in certain content or broad professional experience necessarily know how to teach and that people learn to teach while teaching 15,18 . It is undeniable that the teacher must possess depth of knowledge of their subject matter, but not only of it.…”
Section: Discussionmentioning
confidence: 93%
“…Also in the wake of verifying the need for teacher training, nurses valued the acquisition of didactic-pedagogical knowledge as subsidiary to the teacher's instrumentality. When at stake, the knowledge that underpins the teaching work, and the exclusive acquisition of technical knowledge in the Nursing area, or any other areas, are insufficient 18,22 . Therefore, it is fundamental to approach and deepen on knowledge that goes beyond the Nursing profession to support and strengthen the teaching practice.…”
Section: /14mentioning
confidence: 99%
“…Apesar dos participantes adotarem as MA no cotidiano, relataram na última amostragem do estudo algumas dificuldades que, para Barros e Soares, (2008), na falta de capacitação específica na preceptoria, talvez seja a maior dificuldade no processo ensinoaprendizagem, o que auxilia para a prática pouco produtiva e desestimulante nesse processo. Scarton et al, (2020) na importância da formação permanente dos preceptores no processo ensino-aprendizagem, com sentido do saber, fazer e aprender de forma educativa.…”
Section: Enfermagemunclassified
“…Diante do exposto, o Ensino Superior precisa desenvolver novas estratégias e caminhos para a formação, visto que esta não pode se esgotar em habilidades técnicas e científicas, mas deve se adequar às novas exigências e permitir a apreensão de outras competências e aprendizagens que renovem sua prática (Mancilla, Backes & Canever, 2020;Scarton et al, 2020;Backes et al, 2015). Nesse sentido, tal formação precisa transcender uma ação pontual, como algo que gere conhecimentos e resolutividade coletiva.…”
Section: Introductionunclassified